Developing a School-Based Mental Health Promotion Program Through Co-creation Approach - Phuong, Nguyen Lan; Minh, Dang Hoang; Van, Vu Hong; Ha, Ho Thu; Dao, Kieu Thi Anh; Ha, Le Vu; Myers, Christina; Pellini, Arnaldo; Roche, Jose Manuel; Samuels, Fiona (VNU Journal of Science: Education Research, 2023)
School setting is an effective environment for primary mental health care for students. There have been many mental health support programs in schools for students, most of which are predesigned. The objectives of this paper are: i) To introduce the co-creation approach; and ii) To narratively describe the process of co-creating a mental health promotion program for 04 secondary schools and 04 high schools in Nghe An and Khanh Hoa, Vietnam. Students, teachers, parents and local authorities were the involved stakeholders. Mixed methods including narrative research, observations, open-ended and closed-ended questionnaires were used. The results show that using co-creation approach to develop a mental health promotion program is feasible and applicable in Vietnam. Challenges, learnt lessons and discussion about feasibility of the co-creation process to develop the school-based mental health promotion program are also mentioned in the paper.